Exploration of Plane and Solid Figures in Four Umpak Buildings at Penataran Temple - Chandra, Faizal; Marhayati, Marhayati; Nisa', Asfira Zakiatun (International Journal on Teaching and Learning Mathematics, 2023)
Cultural exploration is an activity of extracting data related to a regional culture until a new understanding is obtained. One study that explores culture is ethnomathematics. Ethnomathematics is a study that explains the relationship between culture and mathematical concepts . Plane figures are material that is taught in stages at the elementary school level and strengthened at the junior high school level, while solid figures are material that is taught at the junior high school level. Penataran Temple is a historical relic of three kingdoms namely Kediri, Singasari, and Majapahit. Penataran Temple is located in Penataran Village, Nglegok District, Blitar Regency, East Java Province. One of the buildings in Penataran Temple is the Four Umpak. In ancient times, Empat Umpak in Penataran Temple was used as a place to gather, discuss and rest for the previous kings. This research aims to explore and describe the concept of plane and solid figures in the Empak Umpak building. The research method used is qualitative research with an ethnographic approach. The object of research is the Four Umpak building and its ornaments. The data collection techniques used are observation, measurement, documentation, literature study and interviews. Data analysis techniques used are data collection, data reduction, data presentation, conclusions and verification. Checking the validity of the data using observation persistence and peer checking. The results showed that there are mathematical concepts in the Four Umpak building, namely the concept of plane and solid figures. The concept of plane figures found in the Four Umpak building are rectangles, isosceles trapezoids, and rhombus. While the concept of solid figures contained in the Penataran Temple building is a truncated rectangular pyramid and a rhombic prism.